The Effects of Thermal Effluent on Marine Diatoms and Bacteria - Choon Weng, Lee, (Malaysian Journal of Science, 2003)
In this study, the effects of thermal effluent on the abundance and diversity of microbes (diatoms and bacteria) are investigated. The abundance of diatoms (5.3 Ã¢â‚¬â€ 16 x $10^5$ cells $l^{-1}$) and bacteria (110 Ã¢â‚¬â€ 2500 cfu $ml^{-1}$) showed reduction near the thermal effluent outfall (Ã¢â‚¬â€56 and Ã¢â‚¬â€96%, respectively). However, the effects of thermal effluent are limited to <200 m from the outfall.